2021
DOI: 10.1021/acsabm.1c00869
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Group-Directed Diversity in the Morphology of Self-Assembled Ant-Aib Dipeptides: Garland-Like Architecture and Nanovesicle Formation

Abstract: The morphology and molecular organization of a set of different N-terminal protecting groups containing dipeptides were investigated. The dipeptides consisted of two rigid noncanonical amino acids, Ant and Aib (X-Ant-Aib-OMe; Ant: anthranilic acid and 2-aminobenzoic acid, Aib: 2-aminoisobutyric acid). The change of the N-terminal protecting groups (X = Boc (peptide 1), N α-fluorenylmethoxycarbonyl (Fmoc) (peptide 2), o-NBS (peptide 3), and p-NBS (peptide 4); NBS = nitrobenzyl sulfonyl group) displayed a charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…1−3 Supramolecular self-assembly based on small peptides creates significant interest because of chemical diversity, cost-effectiveness, and convenient modulations compared to other molecules. 4 Peptide self-assembly offers various nanostructures 5−9 including nanowires, 10 nanofibrils, 11,12 nanoribbons, 13 nanospheres, 14 nanotapes, 15 nanobelts, 16 nanovesicle, 17 and nanotubes 18 depending on the internal and external forces. Peptide nanostructures typically exhibit good biocompatibility, low toxicity, low immunogenicity, biodegradability, and target specificity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−3 Supramolecular self-assembly based on small peptides creates significant interest because of chemical diversity, cost-effectiveness, and convenient modulations compared to other molecules. 4 Peptide self-assembly offers various nanostructures 5−9 including nanowires, 10 nanofibrils, 11,12 nanoribbons, 13 nanospheres, 14 nanotapes, 15 nanobelts, 16 nanovesicle, 17 and nanotubes 18 depending on the internal and external forces. Peptide nanostructures typically exhibit good biocompatibility, low toxicity, low immunogenicity, biodegradability, and target specificity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Molecular self-assembly is a procedure for creating ensembles of nanostructures, where molecules autonomously assemble through diverse noncovalent interactions (van der Waals, electrostatic, H-bonding, π–π stacking, and hydrophobic interactions). Supramolecular self-assembly based on small peptides creates significant interest because of chemical diversity, cost-effectiveness, and convenient modulations compared to other molecules . Peptide self-assembly offers various nanostructures including nanowires, nanofibrils, , nanoribbons, nanospheres, nanotapes, nanobelts, nanovesicle, and nanotubes depending on the internal and external forces. Peptide nanostructures typically exhibit good biocompatibility, low toxicity, low immunogenicity, biodegradability, and target specificity. Consequently, they find widespread applications in drug delivery, tissue engineering, biomedical, cell culture, nanoelectronics, and sensors .…”
Section: Introductionmentioning
confidence: 99%
“…11 We recently described the protecting group-directed diversity of supramolecular structures and morphologies of Ant-Aib di-peptides. 12 Moreover, incorporation of Ant in hIAPP 8–37 increases anti-amyloidogenic properties. 13 Kumar et al reported anthranilamide-based short peptides forming self-organized hydrogels, which act as antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%